Assessing health literacy in indigenous Sesotho-speaking dialysis patients in South Africa: a multi-centre, cross-sectional study - Van Rensburg, Elsabet; Reid, Marianne; Pienaar, Melanie; Nel, Mariette (African Journal of Nephrology, 2022)
Background: Limited health literacy is associated with poor health outcomes in dialysis patients. In Africa, including South Africa, dialysis patients’ health literacy levels are unknown. The objectives were to assess the general health literacy levels of Sesotho-speaking patients with end-stage renal disease (ESRD) and the associations between haemodialysis (HD) and peritoneal dialysis (PD) patients at private and public dialysis centres according to demographic variables, health literacy levels and the appraisal and understanding of health information in the Free State province of South Africa. Methods: The Sesotho Health Literacy Test, an indigenous, context-specific general health literacy test that focuses on appraisal and understanding of information, was used in this multi-centre, cross-sectional study. 263 Sesotho-speaking ESRD patients from the private and public healthcare sectors were conveniently selected. Frequencies and percentages for categorical data, using the Chi-square or Fisher’s exact tests, and medians and percentiles were calculated per group using the Kruskal-Wallis test. Results: Of the 263 respondents, 109 received HD in the private and 88 in the public healthcare sector, whereas three received PD in the private and 63 in the public healthcare sector. Most of the respondents presented with low (n=34, 12.9%) and moderate (n=130, 49.4%) health literacy levels. No significant statistical associations were found between the health literacy levels of HD and PD respondents (P = 0.801) or the healthcare sector groups (P = 0.584). Dialysis patients’ education levels (P < 0.001) and their scores obtained in appraisal and understanding questions (P < 0.001) were significantly associated (P < 0.001) with limited health literacy levels.